Morphology and Molecular Phylogenetic Analysis of Deep-Sea Purple Gorgonians (Octocorallia: Victorgorgiidae) from Seamounts in the Tropical Western Pacific, with Description of Three New Species - Li, Yang; Zhan, Zifeng; Xu, Kuidong (Frontiers in Marine Science, 2020)
Members of Scleraxonia Studer, 1887 are one of the most dominant megafaunal taxa on seamounts, but their diversity and spatial distribution are poorly known in the tropical Western Pacific. Among this group, the family Victorgorgiidae Moore et al., 2017 is typically characterized by josephinae clubs in their polyp tentacles and a remarkable purple color but remains one of the most poorly known scleraxonian taxa currently. Victorgorgiidae contains only the genus VictorgorgiaLópez-González and Briand, 2002 and six species. Here we describe three new species of Victorgorgia, V. fasciculata sp. nov., V. iocasica sp. nov., V. flabellata sp. nov., and re-describe V. eminensMoore et al., 2017, based on samples collected from four seamounts in the tropical Western Pacific, and evaluate their phylogenetic position using sequence data of mtMutS and COI genes. These new species are distinguished from each other and congeners by the sclerite forms and sizes, colony characters and polyp arrangement, and particularly the sclerites in the polyps and medulla are found to be most informative. Phylogenetic analyses indicate that V. flabellata sp. nov. is the sister group of V. iocasica sp. nov., and V. eminensMoore et al., 2017 showed a close relationship with Victorgorgia sp. GU563313. However, genetic divergence at the species level was found to be inadequate for differentiation of some close species. Each of the four species was found only from a single seamount, suggesting limited biological connectivity among the four seamount gorgoniians. Our study increases our understanding of the species diversity of Victorgorgiidae, and highlights the need for further research on the diversity and zoogeography of the deep-sea gorgonians. V. fasciculata sp. nov. urn:lsid:zoobank.org:act: 6CDEECC5-B96D-4DDF-95D2-32BEC3DBC938. V. iocasica sp. nov. urn:lsid:zoobank.org:act: BB11D217-C298-401F-8E13-849C33B03905. V. flabellata sp. nov. urn:lsid:zoobank.org:act: 2C0FCCF2-33B1-4C2D-AC8E-6737079422F4. urn:lsid:zoobank.org:pub: 39AF43F8-C0C2-4670-BBA0-DC1A7F1FA01B.